Genes involved in the balance between neuronal survival and death during inflammation - Glezer, I. (2007)
Glucocorticoids are potent regulators of the innate immune response, and alteration in this inhibitory feedback has detrimental consequences for the neural tissue. This study profiled and investigated functionally candidate genes mediating this switch between cell survival and death during an acute inflammatory reaction subsequent to the absence of glucocorticoid signaling. Oligonucleotide microarray analysis revealed that following lipopolysaccharide (LPS) intracerebral administration at striatum level, more modulated genes presented transcription impairment than exacerbation upon glucocorticoid receptor blockage. Among impaired genes we identified ceruloplasmin (Cp), which plays a key role in iron metabolism and is implicated in a neurodegenative disease. Microglial and endothelial induction of Cp is a natural neuroprotective mechanism during inflammation, because Cp-deficient mice exhibited increased iron accumulation and demyelination when exposed to LPS and neurovascular reactivity to pneumococcal meningitis. This study has identified genes that can play a critical role in programming the innate immune response, helping to clarify the mechanisms leading to protection or damage during inflammatory conditions in the CNS. © 2007 Glezer et al.